Detection of enteroviruses and parechoviruses by a multiplex real-time RT-PCR assay. Issue 2 (April 2015) - Pabbaraju, Kanti; Wong, Sallene; Wong, Anita A.; Tellier, Raymond
Abstract: Detection of all enteroviruses while excluding cross-detection of rhinoviruses is challenging because of sequence similarities in the commonly used conserved targets for molecular assays. In addition, simultaneous detection and differentiation of enteroviruses and parechoviruses would be beneficial because of a similar clinical picture presented by these viruses. A sensitive and specific real-time RT-PCR protocol that can address these clinical needs would be valuable to molecular diagnostic laboratories. Here we report a multiplex nucleic acid based assay using hydrolysis probes targeting the 5′ non-translated region for the detection and differentiation of enteroviruses and parechoviruses without cross-detection of rhinoviruses. This assay has been shown to detect enteroviruses belonging to the different species in a variety of specimen types without detecting the different species of rhinoviruses. Laboratory validation shows the assay to be sensitive, specific, reproducible, easy to set up and uses generic cycling conditions. This assay can be implemented for diagnostic testing of patient samples in a high throughput fashion.